Feasibility of shotgun metagenomics to assess microbial ecology of pediatric tracheostomy tubes. (22nd November 2018) - Wang, James C.; Bergeron, Mathieu; Andersen, Heidi; Tikhtman, Raisa; Haslam, David; Hunter, Tammy; Herr, Andrew B.; de Alarcon, Alessandro
Abstract : Objective: Biofilm formation on medical devices such as tracheostomy tubes (TTs) is a serious problem. The clinical impact of biofilms on the airway is still unclear. Biofilms may play a role in granulation tissue development, recurrent airway infections, and failure of laryngotracheal reconstructions. The microbial ecology on TTs has yet to be elucidated. The purpose of this study was to determine the feasibility of shotgun metagenomics to assess the biodistribution of microorganisms on TTs. Methods: Four TTs were collected from pediatric patients (1.4–10.2 years) with (n = 2) and without (n = 2) granulation tissue formation. Duration of TT placement prior to retrieval from patients ranged from 5 to 365 days. DNA extraction was performed using the MO BIO UltraClean Microbial Isolation (Mo Bio Laboratories, Carlsbad, CA). Library generation using Nextera XT adapters (Illumina Inc., San Diego, CA) and metagenomic shotgun sequencing was performed using the Illumina NextSeq500 (Illumina Inc, San Diego, CA). Salinibacter ruber, a species not found in mammalian microbiome communities, was used as a DNA standard and represented 0.7% to 5.7% of the microbiome, ensuring good quality and abundance of sample DNA. Results: Metagenomic shotgun sequencing was successful for all patients. In TTs associated with granuloma, Fusobacterium nucleatum, Haemophilus influenzae, Moraxella catarrhalis, and Streptococcus pneumoniae were predominant, most of which are considered pathogens. From TTs without granulomas, Neisseria mucosa, Neisseria sicca, Acinetobacter baumannii, and Haemophilus parainfluenzae were identified, primarily consistent with respiratory microbiome. Conclusion: This study reveals that metagenomic shotgun sequencing of biofilms formed on pediatric TTs is feasible with an apparent difference in microbiome for patients with granulation tissue. Further studies are necessary to elucidate the pathogenesis of microbial ecology and its role in airway disease in patients with TTs. Level of Evidence: 2c Laryngoscope, 129:317–323, 2019